Adequacy of sanitation and handwashing facilities in public primary schools: case of Tharaka Nithi County, Kenya - Mureithi Njeru, Amos; Juma, Joseph; Mugo, Judy; Odongo, Alfred Owino (International Journal Of Community Medicine And Public Health, 2023)
Background: Hygiene as practices and conditions contribute to the upholding of population health or prevention of disease outbreak. The implication of sanitation needs to the population tends to weigh heavily on the children population due to their vulnerability to pathogens. Methods: Analytical cross-sectional study design was used and 219 participants in the selected public primary schools participated in the study. Data was collected using administered structured questionnaire, observation and Key Informant Interview. Quantitative data analysis was conducted using SPSS version 26.0 and involved univariate and bivariate analysis. Bivariate analysis was done through logistic regression was used to test the significance of the association between the dependent and independent variables (p<0.05). Qualitative data was analyzed by thematic content analysis. Results: More than three quarter 171 (78.1%) were day school with 40 (18.3%) and 54 (24.7%) of school having between 150-179 boys and 180-209 girls respectively. Slightly less than half 104 (47.5%) of schools had less than 5 toilets for boys and 90 (41.1%) of schools had between 5-10 toilets for girls, 112 (51.1%) of schools had water available for hand washing outside the latrines/toilets. Schools with 120-149 boys and 210-239 girls were more likely to avail water for handwashing outside the toilets. Conclusions: Schools lack sanitary facilities, water, soap and protective clothing, leading to poor sanitation levels, further, schools with scarcity of water and soap for hand washing are at risk of contamination, leading to the spread of diseases like cholera.